KEBERADAAN KELURAHAN DITINJAU DARI UNDANG-UNDANG NO. 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH (STUDI KASUS, KELURAHAN SUNGAI PENUH): EFENDI, S.Sos,.M.Si - EFENDI (LPPM STIA Nusantara Sakti, 2020)
The results of the study showed problems relating to Law No.23 of 2014 concerning regional government. The village head had carried out his duties well in carrying out government activities. The Lurah has carried out various government activities that are regulated in legislation and the Lurah has followed various rules that were put in place in the implementation of community empowerment. The Lurah has carried out community empowerment in his territory and one of the collaborations that can be done with the community is by carrying out activities that are in direct contact with the community. The Lurah has led all the village officials very well and the Lurah has also ensured that the services performed to the community are running properly. Maintenance of peace and public order. The Lurah has also carried out his duties in maintaining order in his territory, this needs to be done so that the people can live in peace and peace. Maintenance of infrastructure and public service facilities. The Lurah has carried out his duties in maintaining various facilities around the area.